Drinkers' memory bias for alcohol picture cues in explicit and implicit memory tasks. (1st March 2016) - Nguyen-Louie, Tam T.; Buckman, Jennifer F.; Ray, Suchismita; Bates, Marsha E.
Highlights: Alcohol but not placebo and control beverage impaired explicit memory of pictures. Implicit memory of picture cues was not impaired by any of the three beverages. Explicit memory was greater for alcohol and emotional compared to neutral cues. Implicit memory was faster for alcohol and emotional compared to neutral cues. Results extend the alcohol cue reactivity literature to include memory bias. Abstract: Background: Alcohol cues can bias attention and elicit emotional reactions, especially in drinkers. Yet, little is known about how alcohol cues affect explicit and implicit memory processes, and how memory for alcohol cues is affected by acute alcohol intoxication. Methods: Young adult participants ( N  = 161) were randomly assigned to alcohol, placebo, or control beverage conditions. Following beverage consumption, they were shown neutral, emotional and alcohol-related pictures cues. Participants then completed free recall and repetition priming tasks to test explicit and implicit memory, respectively, for picture cues. Average blood alcohol concentration for the alcohol group was 74 ± 13 mg/dl when memory testing began. Two mixed linear model analyses were conducted to examine the effects of beverage condition, picture cue type, and their interaction on explicit and implicit memory. Results: Picture cue type and beverage condition each significantly affected explicit recall of picture cues, whereas only picture cue type significantly influenced repetition priming. Individuals in the alcohol condition recalled significantly fewer pictures than those in other conditions, regardless of cue type. Both free recall and repetition priming were greater for emotional and alcohol-related cues compared to neutral picture cues. No interaction effects were detected. Conclusions: Young adult drinkers showed enhanced explicit and implicit memory processing of alcohol cues compared to emotionally neutral cues. This enhanced processing for alcohol cues was on par with that seen for positive emotional cues. Acute alcohol intoxication did not alter this preferential memory processing for alcohol cues over neutral cues.